2015
DOI: 10.1186/s12859-015-0632-y
|View full text |Cite
|
Sign up to set email alerts
|

A composite genome approach to identify phylogenetically informative data from next-generation sequencing

Abstract: BackgroundImprovements in sequencing technology now allow easy acquisition of large datasets; however, analyzing these data for phylogenetics can be challenging. We have developed a novel method to rapidly obtain homologous genomic data for phylogenetics directly from next-generation sequencing reads without the use of a reference genome. This software, called SISRS, avoids the time consuming steps of de novo whole genome assembly, multiple genome alignment, and annotation.ResultsFor simulations SISRS is able … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 37 publications
0
38
0
Order By: Relevance
“…For each dataset (Primates, Rodents, Pecora, and Combined), we used the SISRS pipeline to identify putative orthologs and phylogenetically informative sites (Schwartz et al 2015) . SISRS identifies orthologous loci by assembling a "composite genome" from a subsample of reads pooled across all species.…”
Section: Extracting Phylogenetic Data From Wgs Readsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each dataset (Primates, Rodents, Pecora, and Combined), we used the SISRS pipeline to identify putative orthologs and phylogenetically informative sites (Schwartz et al 2015) . SISRS identifies orthologous loci by assembling a "composite genome" from a subsample of reads pooled across all species.…”
Section: Extracting Phylogenetic Data From Wgs Readsmentioning
confidence: 99%
“…In the absence of reference genomes or annotation information, the SISRS bioinformatics pipeline (Schwartz et al 2015) facilitates genome-wide ortholog comparison directly from unannotated whole-genome sequencing (WGS) reads, enabling genome-scale informativeness comparisons among locus types. Using WGS data from focal sets of primates, rodents, and pecora, we identify millions of potentially informative sites in the absence of reference information.…”
Section: Introductionmentioning
confidence: 99%
“…The software package kSNP (178,179) takes a reference-free approach to identifying SNVs by breaking up each genomic data set into k-mers and comparing these k-mers. Another software package, SISRS (180), assembles a composite genome from the sequencing data and uses this assembled composite as a reference for variant calling.…”
Section: Phylogenetics To Phylogenomicsmentioning
confidence: 99%
“…The number of reference genomes available has rapidly increased, but it is not complete 41 in most clades. To avoid the drawbacks of limited reference genomes, several new phylogenetic 42 approaches have been developed that do not require sequence alignments or whole-genome 43 assemblies, such as phylogeny-building approaches using kmers (Fan et al 2015), de novo 44 identification of phylogenetically informative regions (Schwartz et al 2015), and local 45 assemblies of target genes (Allen et al 2015;Johnson et al 2016). These methods can accurately 46 reconstruct known and simulated phylogenies of pure lineages.…”
mentioning
confidence: 99%
“…Alignment and assembly (AA)-free phylogeny-building methods are gaining popularity, 308 but they have not previously been applied to hybrid data. Therefore, we also tested how AA-free 309 phylogenetic methods, such as AAF (Fan et al 2015) or SISRS (Schwartz et al 2015), 310 performed in detecting and visualizing hybrids compared to sppIDer. We found that these 311 methods performed well when given only pure lineages, but when hybrids were included, they 312 either failed completely or produced incorrect phylogenies.…”
mentioning
confidence: 99%